Culture in maternal health promotion: insight from perinatal women in north central Nigeria / Aisha Imam Omoloso, Mohd Khairie Ahmad and Romlah Ramli - Omoloso, Aisha Imam; Ahmad, Mohd Khairie; Ramli, Romlah (2017)
Despite global attention on the importance of culture in health promotion, studies that explicate culture in the light of maternal health from the perspectives of pregnant and post natal women in Nigeria are rarely found in health communication literatures. This study therefore explored the lived experiences of pregnant and post natal women in north central Nigeria to understand the cultural context of the women’s maternal health experience as a means of bringing to fore important elements of their ethnic culture that can be utilised for maternal health promotion. In-depth phenomenological interviews were conducted with 13 women of diverse ethnicity and three themes emerged with the analysis of interview data, through the use of NVivo 10 software. The themes are cultural knowledge and affiliation, cultural description and cultural variation. These themes which reflect the informants’ perceptions of their ethnic culture in relation to maternal health highlight cultural values, strong familial ties, respect for elders, and communal system of handling issues of maternal health as well as level of education as important cultural elements to be considered for maternal health promotion in the area. These findings contribute to existing knowledge on the understanding of culture and cultural sensitivity in maternal health promotion from a contextualised audience perspective. The study submits that taking cognisance of these aforementioned elements of culture in maternal health message design can serve as strategies of facilitating message relevance, comprehension and adoption by the recipients in north central Nigeria. It is recommended that future research explore lived experiences of other community members who form part of the cultural groups and identities of the perinatal women in different parts of Nigeria using both qualitative and quantitative approaches as insights from qualitative data can be complemented by quantitative data which allow for generalisations.